Using Games to Promote English as a Foreign Language Learners’ Willingness to Communicate: Potential Effects and Teachers’ Attitude in Focus - Liu, Fei; Vadivel, Balachandran; Rezvani, Ehsan; Namaziandost, Ehsan (Frontiers in Psychology, 2021)
This study aims to find out the role of games in promoting students’ willingness to communicate (WTC) and their teachers’ attitude toward it. In order to collect the data, the researchers employed a 28-item questionnaire which was given to 60 English as Foreign Language (EFL) learners in an English institute. Then, the students were randomly divided into two groups of 30 learners functioning as control and experimental groups. The students in the experimental group received games in their language lessons and classes whereas control group learners did not. At the end of the term, the same questionnaire was given to the students to know if playing games had a significant impact on their WTC. Besides, the teachers were asked to answer a 30-item questionnaire to investigate their attitudes toward playing games in language classes. The results showed that games played a significant role in improving the EFL leaners’ willingness to communicate. Moreover, most of the teachers in this study believed that games have a positive influence on the students’ attitudes towards learning English and that using them in class serves many educational purposes. In the light of these findings, the researchers suggested using games as energizers and practical activities at the end of class not only to improve enthusiasm for learning, but also to improve the learners’ WTC.